Mechanical improvement of polymer concrete by using aged polyester resin, nanosilica and gamma rays - Martinez-Lopez, Angel; Martinez-Barrera, Gonzalo; Vigueras-Santiago, Enrique; Martinez-Lopez, Miguel; Gençel, Osman; Gençel, Osman (Elsevier, 2022)
It is well-known that polymer resins are products with a limited shelf life and must be sold quickly. Nevertheless, some of them are not sold on time, and are thus held in stock for long periods, which diminishes their properties. Monomers within the polyester resin gradually evaporate, resulting in a reduction in the expected properties. Thus, resins are sold for other purposes different to the initial ones. One alternative in order to retain the original values consists of modifying the unsaturated polyester resin with chemical additives, although such procedures are costly. For these reasons, in this work unsaturated polyester resin was submitted to three different temperatures (room, 60 degrees C and 90 degrees C), during 270 days. At certain age times (30, 90, 180 and 270 days), the physical properties were measured in order to decide the most appropriate resin for producing polymer concrete. In this case the resin was heated at 60 degrees C for 180 days. Polymer concretes were produced with different silica sand/unsaturated polyester resin ratios, namely 70/30, 75/25 and 80/20; the compressive strength and the elasticity modulus were evaluated. The highest compressive strength value (80 MPa), the lowest deformation (0.056 mm/mm) and the highest elasticity modulus (43.8 GPa), were obtained for concretes with 70% silica sand and 30% unsaturated polyester resin. For these concretes, the silica sand was replaced by nanosilica at 0.3%, 0.6% and 0.9% by weight. Finally, polymer concrete specimens with or without nanosilica were exposed to gamma rays at 50, 100 and 150 kGy doses. The highest compressive strength value (84 MPa), and the highest elasticity modulus (46.2 GPa), were obtained for concretes with 0.9 wt% nanosilica and irradiated at 50 kGy, while the lowest deformation (0.048 mm/mm), was obtained with the same nanosilica content but irradiated at 100 kGy. In summary, it is possible to hold the compressive strength values and to notably increase the elasticity modulus for concrete produced with resin aged 180 days, with 0.9 wt% nanosilica, irradiated at 50 kGy.
Keywords: Aged Unsaturated Polyester Resin; Nanosilica; Silica Sand; Gamma Radiation; Mechanical Properties